Strategi Marketing Public Relations Mischief Denim di Masa Pandemi - Tamareisya Setiawan Putri; Maman Chatamallah (UNISBA Press, 2022)
Abstract. The presence of the Covid-19 pandemic crisis has affected Mischief Denim as one of the business sector. In this regard, the activities of a company must continue to run with the role of marketing public relations in it so that they can then maintain their business. Like Mischief Denim did with the “photo contest challenge” program as a marketing public relations program. This study aims to determine the planning, implementation, and reasons for Mischief Denim choosing the “photo contest challenge” program as a marketing public relations strategy during the pandemic. The research method used is a qualitative method with a case study approach. The theory used in this research is marketing public relations, the concept of a three-way strategy, and the concept of the operational process of public relations. Data collection techniques were conducted by interview, observation, literature study and documentation. While the subjects interviewed in this study amounted to two people from the Mischief Denim. The results of this study found that Mischief Denim's marketing public relations strategy planning through the